THE EFFECT OF CURRENT RATIO, TOTAL ASSET TURNOVER, DEBT TO ASSET RATIO, AND DEBT TO EQUITY RATIO ON RETURN ON ASSETS IN PLANTATION SUB-SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Gunawan, Rais; Widiyanti, Marlina; Malinda, Shelfi; Adam, Mohamad (CV. Radja Publika, 2022)
This study aims to analyze and apply the effect of the current ratio (CR), total asset turnover (TATO), debt to asset ratio (DAR), and debt to equity ratio (DER) on return on assets (ROA). The population in this study is plantation companies with 21 companies and a sample of 21 companies. The sampling technique used is a saturated sample/census; that is, all the population is sampled. The data collection technique uses documentation from financial reports published on the IDX's official website, namely www.IDX.co.id. The analysis used is multiple regression analysis. The results of this study indicate that the Current Ratio does not affect ROA, TATO has a positive and significant effect on ROA, DAR has a negative and significant effect on ROA, DER has a positive and significant effect on ROA.